An ontology-based approach for test case management system using semantic technology / Mansoor Abdullateef Abdulgabber Abdulhak - Mansoor Abdullateef, Abdulgabber Abdulhak (2013)
The Ontology-based Test Case Management System has been developed to maximize the use of Semantic Technology in representing and processing individual test cases for automate and reuse purpose. Effective and efficient use of test cases is desirable of any testing process. In order to achieve this an automated test case management system that is ‘knowledgeable’ is needed, where concepts and terms related to testing are important to support automated reasoning about test cases as well as for promoting common understanding among software testing practitioners involved. This thesis presents an ontology-based approach for test case management that leverages on the emerging semantic technology for developing its knowledge component. Under this approach individual test cases are structured in such a way that the important attributes, metadata, as well as linkages to related software artefacts and software testing ontology are all captured and represented using Semantic Web languages. The software testing ontology is constructed using a software testing glossary that is based on IEEE Standard as a basis. As a proof of concept an ontology-based test case management system has been developed based on this approach with the incorporation of novel features such as Automated Information Extraction and Test Case Semantic Search. The Semantic Software Testing Case Management System is found to be useful in representing and managing the Well-Structure Test Case. The thesis also discusses how the system has been validated against its objectives and argues for some perceived benefits it can bring to software testing environments.